The dynamics of the relationship between household decision-making and farm household income in small-scale irrigation schemes in southern Africa - Bjornlund, Henning; Zuo, Alec; Wheeler, Sarah Ann; Parry, Karen; Pittock, Jamie; Mdemud, Makarius; Moyo, Martin (Elsevier, 2019)
Irrigation has been promoted as a strategy to reduce poverty and improve livelihoods in southern Africa. Households’ livelihood strategies within small-scale irrigation schemes have become increasingly complex and diversified. Strategies consist of farm income from rain-fed and irrigated cropping as well as livestock and an increasing dependence on off-farm income. The success of these strategies depends on the household’s ability to make decisions about how to utilize its’ financial, labour, land and water resources. This study explores the dynamics of decision-making in households on-farm household income within six small-scale irrigation schemes, across three southern African countries. Household survey data (n = 402) was analyzed using ordered probit and ordinary least squares regression. Focus group discussions and field observations provided qualitative data on decision-making in the six schemes. We found strong support for the notion that decision-making dynamics strongly influence total household income. Households make trade-offs between irrigation, dryland, livestock and off-farm work when they allocate their labour resources to maximize household income; as opposed to maximizing the income from any individual component of their livelihood strategy, such as irrigation. Combined with the impact of the small plot size of irrigated land, this is likely to result in sub-optimal benefits from expensive investments in irrigation infrastructure. Policy-makers must consider this when developing and implementing new policies.